The Effect of Overweight on Gross Motor Development in Early Childhood - Muniroh, Luluk Laelatul; Kuswanto, Cahniyo Wijaya (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Overweight in children is increasingly recognized as a risk factor for developmental delay, particularly in gross motor skills. This study investigated the correlation between obesity and gross motor development in 5–6-year-old children using a quantitative correlational approach. Data were collected from 15 children selected through purposive sampling of two kindergartens in Bandar Lampung, Indonesia. Gross motor development was assessed using an observational checklist adapted from the Denver II scale. The analysis revealed a very strong positive correlation between overweight and gross motor skill impairment (Pearson r = 0.911, p< 0.001). Regression analysis further confirmed that overweight significantly predicted gross motor developmental delay (F = 14.849, p < 0.001). This finding suggests that overweight significantly impairs children's physical mobility. This study contributes current local data to the growing global concern about pediatric obesity and its developmental consequences. Practical implications include the need for integrated school-based interventions and awareness programs for parents to reduce overweight-related motor deficits in children aged religious